IOP Conference Series: Earth and Environmental Science - Ovcharenko specialist in the field of mechanical engineering Professor-consultant of Yurga technological Institute of Tomsk Polytechnic University, doctor of technical sciences; Ivanov; Mokhovikov specialist in the field of mechanical engineering Head of Department of Yurga technological Institute of Tomsk Polytechnic University, candidate of technical sciences; Yu; Yu Xu; Zhong (2018)
Metal-ceramic composites are the main materials for high-load parts in tribomechanical systems. Modern approaches to extend the operation life of tribomechanical systems are based on increasing the strength and tribological properties of the surface layer having 100 to 200 microns in depth. The essential improvement of the properties occurs when high dispersed structure is formed in the surface layer using high-energy processing. As a result of the dispersed structure formation the more uniform distribution of elastic stresses takes place under mechanical or thermal action, the energy of stress concentrators emergence significantly increases and the probability of internal defects formation reduces. The promising method to form the dispersed structure in the surface layer is pulse electron irradiation in the plasmas of inert gases combining electron irradiation and ion bombardment in one process. The present work reports upon the effect of pulse electron irradiation in plasmas of different inert gases with different atomic mass and ionization energy on the structure and tribological properties of the surface layer of TiC/(Ni-Cr) metal-ceramic composite with the volume ratio of the component being 50:50. It is experimentally shown that high-dispersed heterophase structure with a fraction of nanosized particles is formed during the irradiation. Electron microscopy study reveals that refining of the initial coarse TiC particles occurs via their dissolution in the molten metal binder followed by the precipitation of secondary fine particles in the interparticle layers of the binder. The depth of modified layer and the fraction of nanosized particles increase when the atomic number of the plasma gas increases and ionization energy decreases. The wear resistance of metal-ceramic composite improves in accordance to the formation of nanocrystalline structure in the surface layer.